ANALISIS HUBUNGAN PELANGGAN DALAM STRATEGI BISNIS PADA JOHZO HAIRDRESSING - Hasan, Golan; Christella, Christella; Wen Jun, Ervin Setyawan Al; Randy, Randy (Gapenas Publisher, 2025)
Customer relationship management (CRM) is a crucial aspect in increasing customer loyalty and maintaining business sustainability, especially for companies in the beauty industry sector. This research aims to analyze the implementation of CRM at Johzo hairdressing to understand the effectiveness of the customer relationship strategy implemented. Through observation and interviews with the company's management and customers, this research identifies factors that contribute to the success and challenges in building customer relationships. The results show that optimal CRM implementation can increase customer satisfaction, which in turn has an impact on company loyalty and competitiveness. However, there are still obstacles such as technological limitations and lack of in-depth understanding of CRM strategies. Thus, this study recommends strengthening education related to CRM and increasing the utilization of digital technology in managing customer relationships.